Efektivitas Pelaksanaan Putusan oleh Tergugat Selaku Badan atau Pejabat TUN di Pengadilan Tata Usaha Negara Denpasar - Putu Ayu Sintya Pradnya Dewi; Anak Agung Sagung Laksmi Dewi; Luh Putu Suryani (Jurnal Preferensi Hukum, 2024)
The State Administrative Court is tasked with resolving cases in the field of governance, Article 116 of Law Number 51 of 2009 concerning State Administrative Courts regulates administrative mechanisms, but in practice it is still less effective due to non-compliance by officials. In connection with this, what are the factors that cause non-compliance with the implementation of decisions by the defendant as a state administrative agency or official at the Denpasar State Administrative Court? And how are efforts made to improve the effectiveness of the implementation of decisions in the Denpasar State Administrative Court? This research uses empirical methods with sociological, conceptual and statutory approaches. The research location was conducted at the Denpasar State Administrative Court. Related data collected in this study using primary data and secondary data. The results showed that the factors that caused the defendant's non-compliance with the execution of the decision were due to indications that the existence of the State Administrative Court as a control institution was less effective and the lack of legal obedience of state administrative officials. Therefore, there is a need for a special institution to optimize the execution supervision mechanism.